2014
DOI: 10.1371/journal.pone.0111559
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Nano-Emulsion Curcumin in Mice Suppresses Inflammatory-Induced NFκB Signaling and Macrophage Migration

Abstract: Despite the widespread use of curcumin for centuries in Eastern medicine as an anti-inflammatory agent, its molecular actions and therapeutic viability have only recently been explored. While curcumin does have potential therapeutic efficacy, both solubility and bioavailability must be improved before it can be more successfully translated to clinical care. We have previously reported a novel formulation of nano-emulsion curcumin (NEC) that achieves significantly greater plasma concentrations in mice after ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…30,122,153,154 Curcumin has multiple health benefits, including antioxidant, antimicrobial, anti-inflammatory, anti-aging, anti-Alzheimer, anti-Parkinson, and anticancer activities. 30,32,94,144,[153][154][155] A lower retention time in circulation leads to the lower therapeutic potential of this compound. 139,144 Reducing the size of the curcumin compound to the nanolevel and formulating it with polyesters leads to higher bioavailability in systemic circulation.…”
Section: Nanocurcuminmentioning
confidence: 99%
See 4 more Smart Citations
“…30,122,153,154 Curcumin has multiple health benefits, including antioxidant, antimicrobial, anti-inflammatory, anti-aging, anti-Alzheimer, anti-Parkinson, and anticancer activities. 30,32,94,144,[153][154][155] A lower retention time in circulation leads to the lower therapeutic potential of this compound. 139,144 Reducing the size of the curcumin compound to the nanolevel and formulating it with polyesters leads to higher bioavailability in systemic circulation.…”
Section: Nanocurcuminmentioning
confidence: 99%
“…30,32,94,144,[153][154][155] A lower retention time in circulation leads to the lower therapeutic potential of this compound. 139,144 Reducing the size of the curcumin compound to the nanolevel and formulating it with polyesters leads to higher bioavailability in systemic circulation. 122,123,144,155 Many studies have confirmed that nanosizing curcumin enhances bioavailability and therapeutic efficiency for many diseases including PD.…”
Section: Nanocurcuminmentioning
confidence: 99%
See 3 more Smart Citations